Painful, irreducible inguinal swelling: a rare presentation of retroperitoneal venous malformation in a boy. A Case Report - Muhammad Azhar; Aisha Jamil (Journal of the Pakistan Medical Association, 2021)
ABSTRACT: A 10-year-old boy presented in emergency department with a painful and irreducible inguinal swelling on right side. Exploration revealed a reddish-blue tissue mass protruding through the deep ring extending into base of scortum. On further dissection swelling was found to be in continuity with multifocal retroperitoneal vascular malformations scattered along the posterior and lateral abdominal wall. This swelling was excised and histopathology result confirmed the diagnosis of venous variety of vascular malformation. This is an unusual case of a retroperitoneal venous malformation in a child, clinically mimicking as strangulated inguinal hernia. Key Words: children, inguinal hernia, retroperitoneal vascular malformation Continuous...